Anticarcinogenic effects of ursodeoxycholic acid in pancreatic adenocarcinoma cell models - Kovács, Patrik; Schwarcz, Szandra; Nyerges, Petra; Bíró, Tímea Ingrid; Ujlaki, Gyula; Bai, Péter; Mikó, Edit (Frontiers in Cell and Developmental Biology, 2024)
Changes to the composition of the microbiome in neoplasia, is termed oncobiosis, may affect tumor behavior through the changes to the secretion of bacterial metabolites. In this study we show, that ursodeoxycholic acid (UDCA), a bacterial metabolite, has cytostatic properties in pancreatic adenocarcinoma cell (PDAC) models. UDCA in concentrations corresponding to the human serum reference range suppressed PDAC cell proliferation. UDCA inhibited the expression of epithelial mesenchymal transition (EMT)-related markers and invasion capacity of PDAC cells. UDCA treatment increased oxidative/nitrosative stress by reducing the expression of nuclear factor, erythroid 2-like 2 (NRF2), inducing inducible nitric oxide synthase (iNOS) and nitrotyrosine levels and enhancing lipid peroxidation. Furthermore, UDCA reduced the expression of cancer stem cell markers and the proportion of cancer stem cells. Suppression of oxidative stress by antioxidants, blunted the UDCA-induced reduction in cancer stemness. Finally, we showed that UDCA induced mitochondrial oxidative metabolism. UDCA did not modulate the effectiveness of chemotherapy agents used in the chemotherapy treatment of pancreatic adenocarcinoma. The antineoplastic effects of UDCA, observed here, may contribute to the induction of cytostasis in PDAC cell models by providing a more oxidative/nitrosative environment.